2011
DOI: 10.1007/s00167-011-1621-y
|View full text |Cite
|
Sign up to set email alerts
|

Expectation, satisfaction and clinical outcome of patients after total knee arthroplasty

Abstract: This study has shown that patient satisfaction correlates well with the clinical outcome according to the KSS, WOMAC and SF-36. The indication for TKA should consider the general health, emotional role and knee function of the patients as well in order to predict patient's outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
123
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 32 publications
14
123
1
4
Order By: Relevance
“…(36,37) The latter has been shown to correlate well with patient satisfaction. (38) Although the use of these scales may indicate improvement in the majority of patients, (14,35) there remains a significant proportion of patients who are dissatisfied with the outcome of the TKA. (14)(15)(16)35) In fact, the dissatisfaction rate for TKA has been reported to be as high as 19%.…”
Section: Discussionmentioning
confidence: 99%
“…(36,37) The latter has been shown to correlate well with patient satisfaction. (38) Although the use of these scales may indicate improvement in the majority of patients, (14,35) there remains a significant proportion of patients who are dissatisfied with the outcome of the TKA. (14)(15)(16)35) In fact, the dissatisfaction rate for TKA has been reported to be as high as 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have sought to predict patient outcomes based on various preoperative patient characteristics, including radiographic findings, knee function scores, mental health, and socioeconomic status. 14,[17][18][19][20][21][22][23][24] Each of these variables has shown to have some predictive value but each has significant limitations. The situation is further complicated by the relatively weak association between symptoms of patients with OA and radiographic findings.…”
Section: Introductionmentioning
confidence: 99%
“…1,14 Although other modes of treatment such as conservative and surgical treatment exists the definitive therapy is joint replacement, and TKA has been shown to be an effective treatment option. 2 Hence many different scores and methods were developed to assess the outcome of this procedure, including the surgeons questioning the patient about his illness and treatment 8 and objective scales such as WOMAC,KSS, SF-36 etc which have shown some degree of correlation with patient satisfaction 17 , but still some patients are dissatisfied, some studies report a dissatisfaction rate of 19% 7,8,9,16 And it is also known that there is a dissonance between the surgeon reported outcomes and patient reported outcomes. In a study by Yuan et al, it is reported that the outcome of 60 patients satisfaction to be 91% [9] while Nunez et al in a study of 112 patients report satisfaction rate to be 86% 16 Which are similar to our study results of 91.74%.…”
Section: Discussionmentioning
confidence: 99%